Biological sex: an understudied factor driving disease susceptibility in pigs. (16th June 2022) - Moeser, Adam J; Roney, Andrew; Fardisi, Mahsa; Thelen, Kyan
Abstract: Biological sex is a major host factor influencing risk for infectious disease-associated mortality, and chronic inflammatory and metabolic diseases. Research in human and rodent models –has revealed sex differences that exist across organ systems during health and disease that may contribute to sex biases in disease risk. Despite the robust and growing literature on the role of sex as a risk factor in human disease, comparatively little attention has been focused on investigating the role of biological sex in disease susceptibility in agriculturally important animal populations such as the pig. To date, comparisons between sexes have focused on carcass composition, growth rate, and feed efficiency in pigs. However, there is a large gap in the literature regarding the effects of biological sex on other integral aspects of health and disease. The objective of this review is to highlight the available literature reporting sex differences in pig health and biology with an emphasis on sex differences in mortality, immunity, and gastrointestinal (GI) physiology and to address biological sex as a significant biological variable in disease risk and research study design. A basic overview of the biology of sex differences including the major hormonal and genetic/chromosomal mechanisms of sexual differentiation and the developmental periods in which sex differences emerge will be covered. This review will also discuss how production-relevant management and environmental factors (e.g., wean age, castration, stress, and nutrition) interact with biological sex to shape host immune and GI development and function. Perceived gaps in knowledge and areas of future research will also be discussed. Lay Summary: It has become increasingly evident that females and males differ in their susceptibility to disease and mortality. Females typically have higher survivability rates during pandemics and environmental challenges compared with males. In many cases, females mount a greater immune response compared with males which may have survival benefits, but at the same time may predispose them to chronic inflammatory disorders. Despite this accumulated knowledge on the key role that sex plays on immunity and disease outcomes in humans, little attention has been placed on sex differences in agriculturally important species such as the pig. The objective of this review is to highlight the literature on sex differences in swine with a focus on mortality, immunity, and GI health. Abstract : A major factor determining risk for disease in people is biological sex but its influence on agriculturally important animals such as the pig is poorly understood. This review addresses the current literature on sex differences in pig mortality, immunology, and gastrointestinal function and its potential significance to understanding disease susceptibility in pig production.